Prevalence of Hearing Loss Among a Representative Sample of Canadian Children and Adolescents, 3 to 19 Years of Age. Issue 1 (January 2017) - Feder, Katya Polena; Michaud, David; McNamee, James; Fitzpatrick, Elizabeth; Ramage-Morin, Pamela; Beauregard, Yves
Abstract : Objectives: There are no nationally representative hearing loss (HL) prevalence data available for Canadian youth using direct measurements. The present study objectives were to estimate national prevalence of HL using audiometric pure-tone thresholds (0.5 to 8 kHz) and or distortion product otoacoustic emissions (DPOAEs) for children and adolescents, aged 3 to 19 years. Design: This cross-sectional population-based study presents findings from the 2012/2013 Canadian Health Measures Survey, entailing an in-person household interview and hearing measurements conducted in a mobile examination clinic. The initial study sample included 2591 participants, aged 3 to 19 years, representing 6.5 million Canadians (3.3 million males). After exclusions, subsamples consisted of 2434 participants, aged 3 to 19 years and 1879 participants, aged 6 to 19 years, with valid audiometric results. Eligible participants underwent otoscopic examination, tympanometry, DPOAE, and audiometry. HL was defined as a pure-tone average >20 dB for 6- to 18-year olds and≥ 26 dB for 19-year olds, for one or more of the following: four-frequency (0.5, 1, 2, and 4 kHz) pure-tone average, high-frequency (3, 4, 6, and 8 kHz) pure-tone average, and low-frequency (0.5, 1, and 2 kHz) pure-tone average. Mild HL was defined as >20 to 40 dB (6- to 18-year olds) and≥ 26 to 40 dB (19-year olds). Moderate or worse HL was defined as >40 dB (6- to 19-year olds). HL in 3- to 5-year olds (n = 555) was defined as absent DPOAEs as audiometry was not conducted. Self-reported HL was evaluated using the Health Utilities Index Mark 3 hearing questions. Results: The primary study outcome indicates that 7.7% of Canadian youth, aged 6 to 19, had any HL, for one or more pure-tone average. Four-frequency pure-tone average and high-frequency pure-tone average HL prevalence was 4.7 and 6.0%, respectively, whereas 5.8% had a low-frequency pure-tone average HL. Significantly more children/adolescents had unilateral HL. Mild HL was significantly more common than moderate or worse HL for each pure-tone average. Among Canadians, aged 6 to 19, less than 2.2% had sensorineural HL. Among Canadians, aged 3 to 19, less than 3.5% had conductive HL. Absent DPOAEs were found in 7.1 E % of 3- to 5-year olds, and in 3.4 E % of 6- to 19-year olds. Among participants eligible for the hearing evaluation and excluding missing data cases (n = 2575), 17.0% had excessive or impacted pus/wax in one or both ears. Self-reported HL in Canadians, aged 6 to 19, was 0.6 E% and 65.3% (aged 3 to 19) reported never having had their hearing tested. E indicates that a high sampling variability is associated with the estimate (coefficient of variation between 16.6% and 33.3%) and should be interpreted with caution. Conclusions: This study provides the first estimates of audiometrically measured HL prevalence among Canadian children and adolescents. A larger proportion of youth have measured HL than was previously reported using self-report surveys, indicating that screening using self-report or proxy may not be effective in identifying individuals with mild HL. Results may underestimate the true prevalence of HL due to the large number excluded and the presentation of impacted or excessive earwax or pus, precluding an accurate or complete hearing evaluation. The majority of 3- to 5-year olds with absent DPOAEs likely had conductive HL. Nonetheless, this type of HL which can be asymptomatic, may become permanent if left untreated. Future research will benefit from analyses, which includes the slight HL category, for which there is growing support, and from studies that identify factors contributing to HL in this population. Abstract : Supplemental Digital Content is available in the text.